Student’s strategies in online autonomous English language learning - Inayati, Nina; Rachmadhani, Rachyani Ayulis; Utami, Berliana Nurmustika (JEES (Journal of English Educators Society), 2021)
This study investigates the integration of online technology by English language learners, especially those done in autonomous learning. To be more specific, this study aims to discover how systematic is students’ strategies in online autonomous language learning and the supports they expect from the educational institutions and teachers/lecturers in terms of conducting effective online autonomous learning. This study mainly employs survey design which is supported by interview. The population of the study was the undergraduate students of English Language Education Department in a private university in Malang, East Java, Indonesia. The findings suggest that learners were less systematic in their strategy use when conducting autonomous language learning. They showed lack of long term goal setting and reported difficulty in evaluation, and mostly resort to short term planning, resource finding and execution of learning. For the reasons, avoidance of classroom-like feeling and not knowing how to evaluate was repeatedly noted. Further, they also reported high expectation of teachers and institutions’ support and assistance in conducting autonomous language learning. The current study and some previous studies in the area have noted that learners tend to consider goal setting and evaluation as teachers’ areas, influenced by the fixed curriculum imposed in schools and university. As such, some flexibility in curriculum enactment is proposed and stronger intervention by teachers and institutions to support learners’ autonomy are proposed.